Choice making in Rett syndrome: a descriptive study using video data - Urbanowicz, A.; Ciccone, N.; Girdler, Sonya; Leonard, H.; Downs, Jennepher (Informa Healthcare, 2018)
Purpose: To describe the choice-making abilities of girls and women with Rett syndrome. Method: Females with Rett syndrome registered with the Australian Rett Syndrome Database with a pathogenic MECP2 mutation were included in this study. Video clips showing choice making in 64 females at a median age of 11.6 years (range 2.3–35.6 years) were analysed. Video clips were coded for the location and nature of the choice-making interaction, and the actions of the communication partner and female with Rett syndrome. Results: The majority (82.8%, 53/64) of females made a choice, most using eye gaze. Just under half (24/53) used one modality to communicate their choice, 52.8% used two modalities and one used three modalities. Of those who made a choice, 50% did so within 8 s. The length of time to make a choice did not appear to vary with age. During choice making, 57.8% (37/64) of communication partners used language and gestures, 39.1% (25/64) used only language and two used language, gestures and symbols within the interaction. Conclusions: The provision of adequate time allowing for a response and observation for the use of multiple modalities could promote effective choice making in females with Rett syndrome.